PEREMPUAN DENGAN PERAN GANDA DALAM KELUARGA (STUDI KASUS ISTRI PETANI DI KELURAHAN PATTAPANG KABUPATEN GOWA - Nurmi, Nurmiati (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this research is to (1) Identify the positive and negative impacts of women's dual roles on children's education (2) Explain the influence of women's dual roles on children and (3) Provide recommendations for policies and programs that support women's well-being. The method used in this research is qualitative descriptive with data collection techniques including in-depth interviews, participatory observation, and documentation. The sample used in this study consists of fiftheen women or wives who have dual roles, like traders. Research findings reveal that working women can contribute to the economic well-being of their families, but they also have both positive and negative impacts on their children's education. Efforts that can be made to improve the welfare of women include providing training to acquire skills such as sewing, offering business capital loans, forming joint business groups, and providing social support. Key words: Women; Dual Role; Farmer; Family.